A three-component reaction of phosphorus ylides with isocyanates: facile synthesis of 2-amino-3-carboxylate-4-quinolones. Issue 44 (28th April 2020) - Babu, Kaki Raveendra; Han, Wendan; Chen, Jian-Bo; Li, Yang; Tang, Yuhai; Zhang, Wenquan; Xu, Wenbo; Xu, Silong
Abstract : A three-component catalyst-free reaction between one molecule of phosphorus ylides and two molecules of isocyanates provides a facile synthesis of 2-amino-3-carboxylate-4-quinolones. Abstract : A three-component reaction between one molecule of phosphorus ylides (P-ylides) and two molecules of isocyanates for the rapid assembly of 2-amino-3-carboxylate-4-quinolones is described. The mechanism may involve the addition of a P-ylide to an isocyanate followed by 1, 3-H shift to form a carbamoyl stabilized P-ylide. The intermediate then reacts with another aryl isocyanate via Wittig/ketenimine-ketene rearrangement/6π-electrocyclization/1, 3-H shift to finally afford the 4-quinolones.